Using Facebook Group as a Blended Learning Medium in Teaching Cross-Cultural Understanding in Islamic Higher Education - Tarihoran, Nafan (Universitas Terbuka, 2020)
This study aimed to investigate how social media, in this case, a Facebook group as Blended learning incorporated in teaching at Islamic Higher Education in Indonesia. Sixty-five EFL students participated in this study. The content of cross-cultural and responses in this closed group was analyzed to identify the patterns of interaction, and their responses to e-journaling through a Facebook group. The findings revealed that the students responded positively to this activity and promote the student's sense of the uniqueness of his own culture as a positive value and enables the students to accept the uniqueness of the other cultures. The power of sharing and learning from other students encourages understanding and appreciation of other cultures.Ã‚Â